Analisis Faktor-faktor Penyebab Defisit Anggaran Penganggaran Belanja Daerah (APBD) Pemerintahan Provinsi Sumatera Utara Tahun Anggaran 2011-2014 - Anggia Ramadhan; Nadia Ika Purnama (CERED Indonesia Institute, 2021)
This study aims to determine the effect of revenue sharing, the realization of local revenue and regional expenditure on the APBD budget deficit in the Provincial Government of North Sumatra for the 2011-2014 fiscal year. This study uses secondary data from BPS and BAPPEDA North Sumatra. The population in this study is the Provincial Government Budget of North Sumatra for the 2011-2014 Budget Year. The method of analysis used in this research is multiple regression method. The results of this study indicate that the revenue-sharing and regional expenditure variables have a positive effect on the APBD budget deficit in the Provincial Government of North Sumatra, while the realization of regional revenue has a negative effect on the APBD budget deficit in the North Sumatra Provincial Government.